Effects of replacing soybean meal with linseed meal in broiler diet on selected broilers’ blood parameters, meat chemical composition, fatty acid profiles, and sensory characteristics - Negasa Tamasgen (Frontiers in Animal Science, 2022)
The study was conducted with the objective of determining the effects of the dietary replacement of soybean meal with graded levels of linseed meal on selected blood parameters, meat composition, fatty acid profiles, and meat quality of broiler chickens. Cobb500 broilers were fed diets containing linseed meal at 0% (T1), 6.5% (T2), 13% (T3), 19.5 (T4), and 26% (T5), replacing 0% to 100% soybean meal in compound rations for 45 days. The experiment was conducted using a completely randomized design with five treatments, each replicated three times with 12 birds. Blood hematological indices were not affected (P>0.05) by treatment diets while among the blood biochemistry triglyceride and cholesterol concentrations in T1 were higher (P<0.05) than in T3, T4, and T5. Glucose was higher in T3, T4, and T5 than in T1 and T2 (P<0.01). The breast and thigh proximate composition for crude protein (CP), ether extract (EE), ash, carbohydrate, and gross energy were similar (P>0.05) among treatments. The sensory scores for breast and thigh meat samples were not different (P>0.05) among treatments. The palmitic acid content of breast and thigh meat was higher (P<0.05) in T1 and T2 than in the other treatments. Eliadic and stearic acid concentrations in thigh meat were greater (P<0.05) in T1, T2, and T3 than in T4 and T5. The oleic and linoleic acid contents of thigh meat were higher (P<0.05) in T2 and T3 than in the rest of the treatments. Breast linolenic acid was high (P<0.05) in T5 but similar in thigh meat. Total saturated fatty acid (SFA) showed a decreasing trend with an increasing level of linseed meal (LSM) in the ration. The ratio of monounsaturated fatty acid (MUFA) to SFA for breast and thigh was higher in T4 and T5 than in T1 and T2. Breast meat ratio of omega-6 (n-6) to omega-3 (n-3) showed a decreasing trend as the level of LSM replacement for soybean meal (SBM) in the ration increased. Generally, linseed meal replacement levels up to 26% in the broilers’ diet improves the essential fatty acid content of chicken meat without affecting the proximate composition and the chickens’ normal blood indices and does not alter meat sensory attributes.